A Comprehensive Study on Friction Stir Welding: A Review - Sen, Murat; Ozcan, Mehmet Erbil; Yildiz, Yunus Onur; Aver, Melike; Kapan, Sinan; Huseyinoglu, Mesut; Kara, Sertac Emre (Assoc Brasil Soldagem, 2025)
Friction stir welding (FSW) is the most widely used solid-state joining method for sheet and plate-like materials, valued for being a highly adaptable, environmentally sound, and energy-efficient process. The literature has repeatedly shown that FSW is a reliable joining technique for high-demand technological applications, particularly for high-strength aluminum and titanium alloys used in aerospace, which are difficult to join with traditional fusion welding methods. To describe the microstructural changes caused by solid-state FSW, many studies analyze mechanical parameters of FSW joints, including tensile strength, bending, torsion, elasticity, and fatigue responses. In recent years, the push to expand FSW's use, broaden the range of compatible alloy systems, and improve the resulting mechanical properties has led to significant advancements in this joining method. Accordingly, this review study provides a comprehensive investigation into the methodology and the materials relevant to this specific field.
Keywords: Friction stir welding; Friction stir processing; Effects of stir welding; Process modelling